A SECA E AS HUMANIDADES NO PROCESSO DE ACESSO À ÁGUA: AS BARRAGENS DO RIO SALINAS E O DESENVOLVIMENTO REGIONAL - Magalhães, Maria Araci; Lima, Samuel do Carmo (Caminhos de Geografia, 2003)
This work is a synthesis of the dissertation about environmental, social, culture, economical impacts have ocurred in Salinas’region - MG, with the building of the dikes in the Caraíbas, Salinas, Bananal rivers. Check the tranformations have ocurred in the landscapes, in the life conditions of population included and its economical development. Key words: water, lifes, development